Development of vaccines at the time of COVID-19. Issue 1 (17th December 2020) - Almond, Jeffrey; Hacker, Jörg; Harwood, Colin; Pizza, Mariagrazia; Rappuoli, Rino; Ron, Eliora Z; Sansonetti, Philippe; Vanderslott, Samantha; Wieler, Lothar H
ABSTRACT: In December 2019, a working group of the European Academy of Microbiology assembled to discuss various aspects of vaccines and vaccinations. The meeting was organised by Jörg Hacker and Eliora Z. Ron and took place in the offices of the Leopoldina (German National Academy of Sciences Leopoldina). Several important issues were addressed and a major part of the discussion focused on the need to develop new vaccines, especially to protect against pathogens that constitute a pandemic threat. Following the rapid and unpredicted spread of COVID-19 in the first seven months of 2020, the need to develop vaccines for pandemic viruses rapidly has been clearly established. Thus, this paper will concentrate on points that were highlighted by the recent COVID-19 pandemic and lessons learnt therefrom. Abstract : Development of vaccines in the times of COVID-19.